Performing autobiography : contemporary Canadian drama - Stephenson, Jenn, 1971- (Toronto [Ont.] : University of Toronto Press, 2013)
Stephenson explores the autobiographical form by analysing seven works by Canadian playwrights written and performed between 1999 and 2009, including Judith Thompson's Perfect Pie, Daniel MacIvor's In On It, and Timothy Findley's Shadows.
1 Narrative Failure and the Loss of an Autobiographical Self: Perfect Pie and The Drawer Boy -- 2 Performative Witnessing to Autobiographies of Trauma: Goodness -- 3 Setting Free Silenced Autobiographical Voices: Eternal Hydra and Shadows -- 4 The Autobiographical Body as a Site of Utopian Performativity: Billy Twinkle -- 5 Self-Authoring Characters in Recursive Autothanatography: In On It -- Coda.
Includes bibliographical references (pages 199-207) and index.
JSTOR
Keywords: Monodramas -- Canada -- History and criticism; One-person shows (Performing arts) -- Canada; Autobiographical drama, Canadian (English) -- History and criticism; Théâtre autobiographique canadien-anglais -- Histoire et critique; Pièces à un seul personnage -- Canada -- Histoire et critique; Spectacles solos -- Canada; DRAMA -- Canadian; PERFORMING ARTS -- Theater -- General; Monodramas; One-person shows (Performing arts); Canada; Monodrama; Drama; Autobiografie; Amerikanisches Englisch; Kanada; Criticism, interpretation, etc